Manajemen Risiko Usaha Pembibitan Tanaman Buah dalam Perkembangan Usaha Mikro Kecil dan Menengah Desa Sukahati (Study Kasus Di Kelompok Tani Tunas Hijau) - Dennistian, Resha (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2019)
This study aims to determine how the risk management process in the Tunas Hijau farmer group and the level of risk management efficiency is carried out. The research used is descriptive qualitative. The results showed that in general the risk management process implemented by the Tunas Hijau farmer group had run well but not yet efficient from the overall risk management carried out. the risk management process implemented by the Tunas Hijau Farmer Group is quite simple and easy, but it requires more attention so that the risk management process can run well. the income of entrepreneurs in the Tunas Hijau farmer group is also very influential with the risk management process imposed by each company management. This shows that risk management has a big influence on the level of income earned by farmers in the Tunas Hijau farmer group.